1999
DOI: 10.1128/jb.181.8.2379-2384.1999
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Effect of Diamines on Transcription of the Cephamycin C Genes from the lat and pcbAB Promoters in Nocardia lactamdurans

Abstract: The diamines putrescine, cadaverine, and diaminopropane stimulate cephamycin biosynthesis in Nocardia lactamdurans, in shake flasks and fermentors, without altering cell growth. Intracellular levels of the P7 protein (a component of the methoxylation system involved in cephamycin biosynthesis) were increased by diaminopropane, as shown by immunoblotting studies. Lysine-6-aminotransferase and piperideine-6-carboxylate dehydrogenase activities involved in biosynthesis of the α-aminoadipic acid precursor were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In contrast, the glycerol feeding strongly enhanced CA as previously reported [21]. Interestingly, the variable concentration of 1,3-diaminopropane in the culture changes that connected production in the favor of either compound [13,22].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, the glycerol feeding strongly enhanced CA as previously reported [21]. Interestingly, the variable concentration of 1,3-diaminopropane in the culture changes that connected production in the favor of either compound [13,22].…”
Section: Introductionsupporting
confidence: 79%
“…The addition of L-lysine, its product, i.e., α-AAA, or its precursor, i.e., diaminopimelate, stimulated the production of CephC in S. clavuligerus [2,11,12]. Similarly, supplementation of the fermentation medium with L-lysine or diamines putrescine, cadaverine, and diaminopropane also enhanced cephamycin production in Nocardia lactamdurans, another cephamycin producer actinomycete [13,14].…”
Section: Introductionmentioning
confidence: 93%
“…Several researchers have promoted production of betalactam antibiotics by adding 1,3-diaminopropane to the culture medium (Leitão et al 1999;Martín et al 2011;Leite, Cavallieri and Araujo 2013). Leitão et al (1999) and Leite, Cavallieri and Araujo (2013) reported a 100% increase in CephC production by S. clavuligerus by adding 5 g l −1 1,3-diaminopropane to the culture medium. Martín et al (2011) added low quantities of 1,3diaminopropane (0.35 and 0.75 g l −1 ) to a Penicillium chrysogenum culture medium and observed, too, that penicillin production increased by approximately 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines also stabilize macromolecules, proteins and membranes modulating electrostatic proteinprotein interactions and affecting DNA-protein interactions (Bassard et al 2010). Leitão et al (1999) studied the effect of 1,3diaminopropane on Amycolatopsis lactamdurans and found that this diamine induces gene expression and stabilizes messenger RNAs. These authors reported, also, high levels of LAT and 1piperideina-6-carboxylate dehydrogenase (P6C dehydrogenase) enzymes and P7 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation